Welcoming schools : a Lebanese model - Ismail, Rana Ahmad (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2002)
The purpose of this case study report was to provide an example, for interested professionals, of the application of inclusive education in a Lebanese private school through the detailed description of the process of establishing the special education program in AL-Kawthar secondary school. The records of the descriptive material might offer some support to alternative interpretations for researchers. They might as well admit subsequent interpretations for professionals whose purpose is different from the researcher. The study did not aim at reaching one specific model for including students with special needs in the Lebanese regular schools. Rather, the study aimed at describing and analyzing the elements of success or failure and the factors leading to them in an inclusion program for students with special need, and to reach common emerging themes worthy of further disciplined study. The study highlighted important lessons that are meaningful for the people involved in inclusive education. In this research study, the prime source of data was open ended in depth interviews. Methodological triangulation process, through document analysis and participant observation data, was utilized to minimize any bias or distortion of the reality of the situation under investigation. A total of 17 participants were interviewed encompassing six students, two parents, three regular teachers, four special education teachers, two paraprofessionals, and one external consultant. Sampling was purposeful where the subjects were chosen to facilitate reaching a wide range of data related to the targeted or emerging themes. Data collected was analyzed with the intention to detect patterns in people's behaviors and perceptions and to organize them into emerging themes. Each interview transcripts was reviewed and formed into brief notes under categories as mentioned by the interviewee. During subsequent transcribed verbatim reading and data analysis of all interviews, the briefing was refined to reach the final common categories as mentioned by each group of interviewees. The brief notes of the common categories were revised to reach the final common themes that relate to the research goals. The final findings of the study conform to the research on the critical elements for successful inclusion and support the emerging research on full inclusion of students with special needs. The results of the study were discussed in relation to implications for future research and practice.
: Mémoire
Keywords: Curricula; Curriculum